Inoculation of maize with phosphate solubilizing bacteria: effect on plant growth and yield - Viruel, Emilce (2014)
Phosphate-Solubilizing Bacteria (PSB) improve plant growth, yield and phosphorus content of several crops, and may be used as bioinoculant to enhance sustainable production. We evaluated the response of maize (Zea mays L.) to PSB inoculation under controlled and field conditions in Tucumán, Argentina. A pot culture experiment was conducted to investigate the effects of seven previously isolated PSB on early development of plants. Seeds were treated with each bacterial strain, and seedlings were harvested 30 days after inoculation. All strains showed a positive effect on plant growth. A significant increment in plant height (45%), shoot dry weight (40%) was determined in plants treated with Pseudomonas tolaasii IEXb, while Pseudomonas koreensis SP28 has remarkably increased P content compared to the uninoculated control. IEXb strain was selected and evaluated under field conditions in combination with triple superphosphate (TSP) as P fertilizer. The presence of IEXb strain stimulated seedling emergence (8%), shoot length (19%), grain yield (44%), 1000-grain weight (18%), total dry biomass (32%) and P content (56%) of maize plants. In general, P. tolaasii IEXb inoculation was more efficient as bioinoculant without P fertilizer than with TSP. These results provide baseline information for future studies of P. tolaasii IEXb as bioinoculant to promote an eco-friendly and sustainable agriculture.